Electricity Supply and Manufacturing Sector Output in Nigeria - Edet, Ene Ene; Henry, James, Tumba; Efefiom, Effiong Charles; Nyiputen, Ishaku Rimamtanung; Bassey, Eduno, Ededet (Energy Economics Letters, 2022)
This study investigated the impact of electricity supply on manufacturing output in Nigeria using data from 1980 to 2019. By augmenting the endogenous growth model production function with key variables affecting manufacturing sector output, such as exchange rate and technology, which previous studies failed to capture. The result of the autoregressive distributed lag (ARDL) model revealed that electricity supply has a negative and insignificant relationship with the manufacturing sector output. Conversely, technology has a positive and significant relationship with manufacturing sector output in the short run. Thus, it was recommended that an adequate and stable supply of electricity and deploying modern technology should be on the front burner of the country’s development policy. This steady supply will not only enhance the growth of the manufacturing sector but also lead to inclusive growth in terms of reducing poverty and unemployment in the Nigerian economy and promoting rapid economic growth.